Analysis of the Effectiveness of Chili Auction Market in Sleman Regency, Special Region of Yogyakarta - Hariyanto Putri, Bunga Pralapita; Budiarto, Budiarto; Suprihanti, Antik (Agro Ekonomi, 2024)
Chili auction market in Yogyakarta was established with the farmer’s cooperative to strengthen the bargaining position of Sleman’s farmers in receiving fair price for chili. Therefore, this study aims to analyze the effectiveness of chili auction market and the problems affecting its implementation. A quantitative approach was used and the location was determined using the purposive method. The sample population comprised chili farmers, who were selected as participants using the accidental sampling method. This study used both primary and secondary data, which were obtained through observation, interviews, and documentation. Subsequently, analysis was carried out using descriptive analysis and a fishbone diagram. The results showed that the effectiveness rate of auction market based on three approaches (external, internal, and technical) reached 70,03%. In addition, the problems affecting its implementation included the low availability of chili due to climate change, pest and disease attacks, the absence of machines or supporting facilities, price information that was not transparent, and the limited capability of auction market administrators. Requirements for traders also needed to be updated regarding regional boundaries to open opportunities for traders outside DIY and Central Java.